The processes of apoptosis and telomerase activity in endometrial cells under different morphological conditions - Chumak, Z. V.; Shapoval, N. V. (Journal of Education, Health and Sport, 2018)
Aging and apoptosis are two mechanisms of a powerful anti - cancer defense. The apoptosis inhibitor is Bcl-2 gene. It expresses in transformed cells, blocks programmed death, promotes the survival of malignant ones. Under experimental conditions, when the Bcl-2 gene was transfected into the endothelial aging cells of mice, there was a decrease in mitochondrial oxidative stress, renewal of the potential of mitochondrial membranes, and improvement of angiogenesis. The objective: to study the expression of the Bcl-2 marker and telomerase activity in endometrial tissue with hyperplasia. Materials and methods. The endometrial tissue samples: 54 with hyperplastic process and 14 patients with a biphasic menstrual ovulatory cycle. Immunohistochemical reactions, real-time PCR with SYBR Green (RQ-TRAP) dye by Wege et al. In endometrial cells with complex non-atypical hyperplasia take place initial disturbances in the processes of programmed cellular death. In complex hyperplasia with atypia in endometrial cells there is inhibition of apoptosis, which can be regarded as a trigger mechanism in the development of cellular atypia. The statistically significant parallelism between the processes of telomerase reactivation in endometrial cells at complex atypical hyperplasia and the existence of telomerase activity in 85% of tumors allows to appraise it as a predictor of oncological process.